1997
DOI: 10.1093/ps/76.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing systems on protein quality of feather meals and hog hair meals

Abstract: Experiments were conducted to evaluate the effects of five commercial processing systems and to a lesser extent, processing temperature within system, on protein quality of feather meals (FM). Two hog hair meals (HH) were also evaluated. True digestibilities of AA were determined with a 48-h excreta collection assay using cecectomized cockerels. Protein efficiency ratio (PER; grams of gain:grams of CP consumed) was determined with chicks by feeding Met-fortified 15% CP diets containing a FM or HH as the sole s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 16 publications
4
58
1
1
Order By: Relevance
“…The obtained low productivity in feather extract medium comparing to that obtained in the poly medium may be reflected the deficiency of the former fermentation medium in required nutrients. Wang and Parsons 1997 reported that the hydrothermal treatment resulted in yielding a product with poor digestibility and variable nutrient quality [29]. Our results are not in accordance with the findings of Poopathi and Abidha [10] perhaps due to the differences in reference media that used as a control.…”
Section: Optimization the Nutritional Requirements Of B Sphaericuscontrasting
confidence: 98%
“…The obtained low productivity in feather extract medium comparing to that obtained in the poly medium may be reflected the deficiency of the former fermentation medium in required nutrients. Wang and Parsons 1997 reported that the hydrothermal treatment resulted in yielding a product with poor digestibility and variable nutrient quality [29]. Our results are not in accordance with the findings of Poopathi and Abidha [10] perhaps due to the differences in reference media that used as a control.…”
Section: Optimization the Nutritional Requirements Of B Sphaericuscontrasting
confidence: 98%
“…In addition, feather wastes are potentially valuable raw materials for the production of nutrient-rich animal feed supplements and amino acids (Shih 1993;Onifade et al 1998). Feather waste processing methods such as steam pressure, chemical treatment and feather milling are cost and labour intensive and may reduce the product's nutritional value by destroying important amino acids (Shih 1993;Wang and Parsons 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of leucine, tyrosine and methionine could result from chymotrypsin-like specificity, but not trypsin or elastase specificity [18]. However, thermal treatment might also affect the composition of bristle substrate, since Wang and Parsons [45] presented slightly elevated concentration of leucine and valine in steam-cooked hog hair meals. High amounts of BCAAs could be obtained as well by alkaline hydrolysis of animal hair [7,46,47].…”
Section: Resultsmentioning
confidence: 99%